Improvement of hardness in Ti-stabilized austenitic stainless steel. (November 2022) - Sharifikolouei, Elham; Sarac, Baran; Micoulet, Alexandre; Mager, Reinhard; Watari-Alvarez, Moyu; Hadjixenophontos, Efi; Burghard, Zaklina; Schmitz, Guido; Spatz, Joachim P.
Graphical abstract: Highlights: Design of a new technique based on planar-flow melt-spinning for the fabrication of metallic glass microfibers. The new technique is based on wetting and formation of thin film on rotating copper wheel followed by simultaneous rupture of the film into microfibers in the range of 1–20 µm. The nature of the new technique makes it possible to fabricate fully amorphous structure from alloy compositions which are not designed for metallic glass formation. We have shown and confirmed the formation of fully amorphous structure in µm-range, from Ti-stabilized 316 stainless steel. The amorphous structure is confirmed by XRD, DTA, TEM. The hardness of the as-purchased stainless steel increased from ∼ 2.5 to ∼ 8.2 GPa after formation of the amorphous structure. The subsequent stepwise heat-treatment on the amorphous stainless steel creates adjacent nanostructured and amorphous grains, observed by TEM. The heat-treated stainless steel shows an even further increase in hardness to ∼ 14.2 Gpa. We believe that both the confinement of dislocation movement in the nanocrystalline grains as well as the absence of dislocations in the amorphous grains contribute to this tremendous increase of hardness in heat-treated stainless steel. Abstract: The high passivation capacity of austenitic stainless steel results in their excellent corrosion resistance. There are many ways to improve the hardness of austenitic stainless steel such as cold rolling or grain refinement. Herein, we explore the possibility of improving the hardness of AISI316-Ti stainless steel by generating an amorphous-nanocrystalline microstructure. First, we have utilized our modified melt-spinning technique to fabricate AISI316-Ti stainless steel microfibers with a fully amorphous structure. Formation of a fully amorphous structure was confirmed by using X-ray diffraction (XRD), differential thermal analysis (DTA), and transmission electron microscopy (TEM). Thermal analysis revealed a glass transition temperature of 437˚C followed by a crystallization peak of 573˚C. Nanoindentation analysis showed a fourfold increase of hardness from the initial value of ≈2.5 ± 0.1 GPa the starting AISI316-Ti stainless steel rod to the hardness of ≈8.2 ± 0.5 GPa for the amorphous AISI316-Ti structure. Further step-size heat treatment on melt-spun (amorphous) stainless steel microfibers generated a microstructure compromising adjacent nanocrystalline and amorphous grains as observed by TEM. Nanoindentation analysis of those fibers has shown an even greater increase in hardness, reaching an average value of ≈14.2 ± 1.0 GPa. We believe that both the confinement of dislocation movement in the nanocrystalline grains as well as the absence of dislocations in the amorphous grains contribute to this tremendous increase of hardness in stainless steel.